DAMPAK PENYALAHGUNAAN OBAT KOMIX DAN MINUMAN TORPEDO DI KALANGAN REMAJA DESA SIMPANG RIMBA KABUPATEN BANGKA SELATAN - Sri Yuliana (Justici, 2021)
ABSTRACT The problem of drug abuse is mostly done by teenagers, especially school children. A survey conducted by the National Narcotics Agency and the University of Indonesia in 15 provinces in Indonesia in 2010 found that dextromethorphan abuse was found among adolescents in high schools and even elementary schools. Dectromethorphan contained in komix when used in excessive doses has an effect similar to the use of ketamine. The resulting effects are confusion, dream-like conditions, a sense of loss of personal identity, speech and movement disorders, disorientation, drowsiness. Ketamine is a type of anesthetic drug, which is generally used in the general anesthesia process to reduce the patient's level of consciousness before or during a medical procedure. The Komix type cough medicine is usually used as a cough reliever but among teenagers, the Komix type cough medicine is being abused. The use of Komix cough medicine media is used as a tool to get a hangover effect. Referring to the description and analysis above, what factors can be classified that cause the abuse of komix drugs and torpedo drinks among youth in Simpang Rimba village? Factors The cause of the abuse of drugs and torpedo drinks in the Simpang Rimba village community is due to low education, lack of concern for parents and families for their children, and unhealthy environmental factors. Making some teenagers in Simpang Rimba village abuse komix drugs and torpedo drinks.